Penyuluhan Fisioterapi Mengenai Cedera Ankle Sprain Pada Atlet Voli Di Komunitas Sonik Universitas Muhammadiyah Surakarta - Ulfa Kumala; Alifah Athiyaturrofi; Tri Mukti Handayani; Wahyu Tri Sudaryanto (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Ankle sprain injury is a musculoskeletal injury that often occurs in sports athletes. Most of these injuries are minor and can be managed by self-medication at home with proper care. Therefore, it is necessary to carry out socialization and education related to the management of ankle sprain injuries in the community. This activity aims to increase the understanding of community members regarding the correct handling of ankle sprains. The method chosen to deliver this activity is by direct lectures and using posters and leaflets as media. Evaluation of the level of understanding of community members was carried out using a post-test sheet consisting of 10 true and false choices. Counseling and education related to ankle sprain injuries had a good impact in increasing the knowledge of members of the UMS SONIK volleyball court community.